EKSPLORASI ETNOMATEMATIKA PADA JAJANAN TRADISIONAL KHAS BANDUNG - Farida, Nur; Nurhayati, Nurhayati; Ariyanto, Saring (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The purpose of this research is to explore the ethnomathematics found in traditional Bandung snacks. Additionally, the author hopes that readers will gain a better understanding of this ethnomathematics. This research was conducted in several locations in the Bandung area. The research method used to explore this ethnomathematics is a descriptive qualitative method, with data collection through observation, interviews, and documentation. The research instruments used were observation sheets and interview guides. After exploring the ethnomathematics in traditional Bandung snacks, the author concluded that these traditional snacks are a rich heritage that must be preserved. The research results show the presence of cultural philosophy and mathematical concepts such as ratios and geometry of plane and solid shapes in traditional Bandung snacks